2007
DOI: 10.1091/mbc.e06-09-0785
|View full text |Cite
|
Sign up to set email alerts
|

Endobrevin/VAMP-8 Is the Primary v-SNARE for the Platelet Release Reaction

Abstract: Platelet secretion is critical to hemostasis. Release of granular cargo is mediated by soluble NSF attachment protein receptors (SNAREs), but despite consensus on t-SNAREs usage, it is unclear which Vesicle Associated Membrane Protein (VAMPs: synaptobrevin/VAMP-2, cellubrevin/VAMP-3, TI-VAMP/VAMP-7, and endobrevin/VAMP-8) is required. We demonstrate that VAMP-8 is required for release from dense core granules, alpha granules, and lysosomes. Platelets from VAMP-8 ؊/؊ mice have a significant defect in agonist-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
183
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 143 publications
(204 citation statements)
references
References 48 publications
(68 reference statements)
11
183
0
4
Order By: Relevance
“…In 2010, Kondkar et al [26] reported that increased levels of vesicle-associated membrane protein 8 (VAMP8)/endobrevin mRNA were associated with platelet hyperreactivity, and that miR-96 could regulate VAMP8/endobrevin mRNA levels in cultured cells. The authors concluded that these data support a role for VAMP8/endobrevin in the heterogeneity of platelet reactivity, and suggest a role for miR-96 in regulating expression of VAMP8, the primary platelet v-SNARE protein involved in the platelet secretion process [27].…”
Section: A Role For Micrornas In Platelet Function?mentioning
confidence: 89%
“…In 2010, Kondkar et al [26] reported that increased levels of vesicle-associated membrane protein 8 (VAMP8)/endobrevin mRNA were associated with platelet hyperreactivity, and that miR-96 could regulate VAMP8/endobrevin mRNA levels in cultured cells. The authors concluded that these data support a role for VAMP8/endobrevin in the heterogeneity of platelet reactivity, and suggest a role for miR-96 in regulating expression of VAMP8, the primary platelet v-SNARE protein involved in the platelet secretion process [27].…”
Section: A Role For Micrornas In Platelet Function?mentioning
confidence: 89%
“…VAMP8 encodes vesicle-associated membrane protein 8, a member of the SNARE complex, that mediates membranemembrane fusion and platelet degranulation. 26,27 SNX19 encodes sorting nexin 19, a member of the nexin family that is involved in intracellular trafficking of membrane vesicles. 28 The sorting nexin 19 protein product has been shown to interact with islet antigen-2, a transmembrane protein tyrosine phosphatase associated with dense core secretory vesicles and a major autoantigen in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently it has been shown that VAMP8 is involved in exocytosis in pancreatic acinar cells (16), mast cells (17,18), cytotoxic T lymphocytes (19), platelets (20,21), and kidney collecting duct epithelia (22).…”
mentioning
confidence: 99%